Case Report: GATA2 deficiency in two families with novel frameshift variants highlighting phenotypic diversity and need for early diagnosis - Morimoto, Miko; Nishikawa, Takuro; Hijikata, Atsushi; Kasabata, Hiroshi; Maeda, Nobuhisa; Kanmura, Shuji; Horikawa, Shogo; Nagahama, Jun; Nakamura, Aki; Nakamura, Tatsuro; Abematsu, Takanari; Nakagawa, Shunsuke; et al. (Frontiers in Immunology, 2025)
BackgroundGATA2 deficiency, a syndrome caused by heterozygous loss-of-function variants in the GATA2 gene, is characterized by immunodeficiency, bone marrow failure, and predisposition to myeloid neoplasms. Its clinical presentation is highly variable, making early diagnosis challenging. Although GATA2 deficiency has been linked to systemic inflammation, gastrointestinal involvement mimicking inflammatory bowel disease (IBD) is extremely rare.Case presentationThis report presented the case of two adolescent boys with no family history of novel heterozygous frameshift GATA2 variants. Notably, Patient 1 initially presented with clinical and endoscopic features strongly suggestive of Crohn’s disease, including weight loss, perianal abscess, and characteristic intestinal ulcers, before developing acute myeloid leukemia with monosomy 7. This is a rare presentation of GATA2 deficiency manifesting initially with Crohn’s disease-like symptoms. Patient 2 presented with intractable cutaneous warts and pancytopenia, later diagnosed as myelodysplastic syndrome with der(1;7)(q10;p10). Both patients harbored novel GATA2 frameshift variants predicted to eliminate the DNA-binding domain, suggesting a loss-of-function mechanism.ConclusionThese cases expand the phenotypic spectrum of GATA2 deficiency and highlight that atypical IBD-like symptoms, including Crohn’s disease-like presentations, may cause an initial manifestation. GATA2 deficiency should be considered in patients with IBD-like symptoms, refractory skin disorders, and hematological abnormalities. Early genetic testing and family screening are essential to ensuring timely diagnosis and curative hematopoietic stem cell transplantation before progression to advanced myeloid disease.